Soil nitrogen affects phosphorus recycling: foliar resorption and plant–soil feedbacks in a northern hardwood forest. Issue 9 (1st September 2015) - See, Craig R.; Yanai, Ruth D.; Fisk, Melany C.; Vadeboncoeur, Matthew A.; Quintero, Braulio A.; Fahey, Timothy J.
Abstract : Previous studies have attempted to link foliar resorption of nitrogen and phosphorus to their respective availabilities in soil, with mixed results. Based on resource optimization theory, we hypothesized that the foliar resorption of one element could be driven by the availability of another element. We tested various measures of soil N and P as predictors of N and P resorption in six tree species in 18 plots across six stands at the Bartlett Experimental Forest, New Hampshire, USA. Phosphorus resorption efficiency ( P < 0.01) and proficiency ( P = 0.01) increased with soil N content to 30 cm depth, suggesting that trees conserve P based on the availability of soil N. Phosphorus resorption also increased with soil P content, which is difficult to explain based on single‐element limitation, but follows from the correlation between soil N and soil P. The expected single‐element relationships were evident only in the O horizon: P resorption was high where resin‐available P was low in the Oe ( P < 0.01 for efficiency, P < 0.001 for proficiency) and N resorption was high where potential N mineralization in the Oa was low ( P < 0.01 for efficiency and 0.11 for proficiency). Since leaf litter is a principal source of N and P to the O horizon, low nutrient availability there could be a result rather than a cause of high resorption. The striking effect of soil N content on foliar P resorption is the first evidence of multiple‐element control on nutrient resorption to be reported from an unmanipulated ecosystem.